Transição capilar : cabelos, consumo e interseccionalidade no ciberespaço - Matos, Lídia de Oliveira (2017)
The capillary transition occurs when the person stops changing the structure of the hair thread using cosmetic products based on chemical substances that give as result a straight hair, and that hair is cared up in a different way from then on. That chemical process gives support to beauty standards imposed to women, affects the self-esteem and raises discussions about consumption, racial and gender relation in brazilian context. Starting from a content survey of two YouTube channels about capillary transition and the native terms that are used to refer to people that passed for this process, I intend to understand the disputes around construction of the meanings of that, analyzing the consumption practices and the intersection between race and gender. This investigation aims on cyberspace, here we highlight the importance of social media, websites and digital platforms as a space for sharing knowledge about hair, ways to take care of it, hairstyles, specific products, and other discussions as feminism, racism and veganism. In this dissertation I introduce a panoramic vision of the studies about hair in Brazil, emphasizing the emergence of hair straightening, outlining the characteristics of the process of capillary transition and the innovations the follows it, exposing how the process has been organized in the cyberspace, articulating a discussion oriented by a perspective of consumption and the intersectionality between race and gender, realizing how the circulation of this contents occurs, the consumption practices and the disputes around native terms.